'DAY WATCH' OR BAYWATCH? A NOTE ON ΗΜΕΡΟΣΚΟΠΟΣ (AR. LYS. 849). (December 2021) - Janse, Mark
Abstract: This article argues that ἡμεροσκόπος at Lys . 849 constitutes a pun based on iotacism, a well-known feature of female speech in fifth-century Athens aptly illustrated by Socrates in Plato's Cratylus . By describing herself as ἡμεροσκόπος 'day watch' pronounced as ἱμεροσκόπος 'lust watch', Lysistrata perverts the military term associated with the occupation-plot to a sexually charged word associated with the strike-plot. Its use would be very appropriate in a scene in which the φαλληφόρια of the men (not just Cinesias' but later on also the Spartan herald's and the Spartan and Athenian delegates') become the subject of a φαλλοσκοπία by the women (not just Lysistrata but later on also the chorus of women) and perforce also by the onlooking audience. Additional contemporary evidence from orthographic mistakes made by schoolboys suggests that Athenian elite women of the late fifth century were the avant-garde of socially prestigious innovations such as iotacism, which would definitively catch on with the male population in the fourth century and change the face of Greek phonology forever.